The Effect of Job Placement, Job Satisfaction and Job Ability on the Performance of As-Shofwan Hospital Employees - Suwandi; Samania Kusma Dewi Sari (Journal of Research in Business, Economics, and Education, 2021)
Health plays an important role in improving people's living standards. To provide the best health services in hospitals, quality resources are needed especially in the current covid-19 which continues to increase. This study aims to determine and analyze the effect of work placement, job satisfaction, and work ability on the performance of As-Shofwan. This research is included in quantitative research because the approach used for research proposals, processes, hypotheses, going to the field, data analysis, data conclusions to writing uses aspects of measurement, calculation, formula, and certainty of numerical data. The research subjects were employees of the As-Shofwan hospital. In this study the population and the sample amounted to 60 people. The data were analyzed using path coefficients with the help of the PLS program. The results showed that work placement and work ability influenced employee performance, while the work ability variable had no effect on employee performance.